Pemanfaatan Pseudomonas putida untuk mendegradasi plastik - Tri Mulyaningsih (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Purpose: to identify and analyze the ability of Pseudomonas sp for plastic waste degradation. Method: This study was a quasi-experimental design with post-test only with control design, using local Pseudomonas sp insulated of Piyungan landfill. Fertilizer media used BHI and selective medium for Pseudomonas Sp namely Cetrimide agar, and characterized by a series of microbact 24E kitt. Isolate elected was suspended with concentration 106CFU/ml, 107CFU/ml, and 108CFU /ml. Furthermore, distributed with volume of 10 ml suspension into each container that containing liquid of standard medium of Basal Salt and plastic (plastic black and white), with control negative (without the addition of bacteria). The incubation time for the plastic to degrade was 49 days at a temperature of 37°C, with periodic harvesting plastic every 7 days. Determination of degradation products was based on the percentage of weight loss plastic after treatment. The data analysis used anova and paired t-test to determine differences in treatment and control. Results: Results of this research showed that there were significant differences between the addition of Pseudomonas putida into media containing plastic compared to control, according to percentage of degradation.The percentage of degradation of the white plastic in the 49 days reached 3.29%, with a dose response of 108 CFU /100mg plastic while the black plastic was degraded with the percentage of degradation reached 4.7%, with a dose response of 107 CFU /100mg black plastic. Conclusion: Pseudomonas putida can degrade the plastic black or white. Percentage degradation of black plastic is greater, faster, and lower Dose response Pseudomonas putida than white plastic.